DAMPAK DIBALIK TINDAK KEKERASAN TERHADAP PEREMPUAN DAN ANAK SERTA SOLUSINYA - Nur Ahmad Muharram (Jurnal Harkat : Media Komunikasi Gender, 2016)
Violence against women is always connoted with gender-based violence. It is not without cause, because the reality of violence against women in any context and the domain is due to the cultural dominance of men against women. Cultural domination is what ultimately makes the lame pattern of relationships between men and women, with a pattern of inferiority and superiority. This is actually happening behind the acts of violence against women is highly implicated in the reality of society over the years.